The impact of architectural modifications on relative resistance to fluid flow in ventricular catheters - Madhavan, Rajesh Kumar; Faryami, Ahmad; Tappen, Nathan; Gopalakrishnan, Pranav; Ajaz, Shaheer H.; Roberts, Christopher; Harris, Carolyn (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionAlthough many ventricular catheter designs exist for hydrocephalus treatment, few standardized studies assess outflow resistance and the impact of design modifications on shunt drainage. This study represents the in-vitro assessment of various architectural modifications on catheter flow rate and pressure, focusing on bulk outflow dynamics and occlusion with whole blood-inoculated cerebrospinal fluid.MethodsCatheters were manufactured utilizing a novel catheter production setup with 16 variations from standard catheters, including but not limited to changes in: hole number, hole dimensions, catheter lumen dimension, and catheter lumen impingement. These catheters were tested in a portable custom-made ventricular catheter testing device to analyze relative resistance to flow between catheter designs. A subset of catheters with varying lumen diameters was tested in 0.30 mL/min saline flow with 2.5% blood to simulate early blood exposure.ResultsWith increasing hole and lumen diameter, we found a significant decrease in overall catheter relative resistance using DIH20 (P < 0.001 and P < 0.002 respectively, n = 5). With increasing lumen diameters, blood assays showed a significant increase in the time to complete obstruction (P = 0.027, n = 5). Lumen impingement, representing one obstruction-based pinch point in the lumen, showed a considerable increase in relative resistance as obstruction diameter increased and lumen diameter at the pinch point decreased (P = 0.001, n = 5). Removal of specific catheter hole rows trended toward an increase relative resistance after 75% of catheter holes were blocked, but the effect in relative outflow resistance is otherwise minimal (P > 0.05, n = 5) and no effect was observed with blocking segments.ConclusionThis study implemented a novel method of rapid catheter manufacturing to systematically produce ventricular catheters with specific catheter architecture. By testing variables independently, we found that catheters with changes to the lumen diameter had the most dramatic shifts in overall relative resistance between catheter designs. Similarly, testing in the acute in-vitro blood assay demonstrated that smaller diameter catheters have a higher propensity to obstruct with blood compared to catheters with larger diameter. Relative resistance impacts fluid outflow efficiency, which may translate to clinical outcomes for hydrocephalus patients. These findings help us understand catheter architectural effects on resistance and inform future designs for specific ventricle morphologies.